Dampak Literasi Digital Instagram @mudahbergaul tentang Kesehatan Mental terhadap Kesadaran Masyarakat - Fitri Wahyu Rahmadania; Fransiska; Kukuh Laksono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The numbers of people suffering from mental health issues such as anxiety, depression, self-harm, suicidal tendency and other mental disorders become a huge problem due to the lack of public awareness as well as the society’s perception that seen as a taboo topic. Mental health become one of the topics that are being discussed among the society especially the MZ generation as technology and social media platforms have evolved. The government engaged in collaborating with private sectors, non-governmental organization (NGO’s), and content creator to educate the public through the digital literation Instagram to encourage the society to become aware of mental health. @mudahbergaul in one of Instagram’s account has been used as digital literation media that purposely to increase public awareness of mental health. The research aims to measure the impact of digital literation Instagram @mudahbergaul on the public awareness related to mental health. The research used quantitative method which used survey as a tool in data collection. The findings showed a significant positive impact of 56,2% between digital literation Instagram @mudahbergaul on the public awareness related to mental health due to several factors such as effective in communication and information accessibility.